North America
This sheet includes a map of North America on one side and maps of the Dominion of Canada, New Brunswick, and Nova Scotia on the other. The first map shows North and Central America in various colors. Mexico and all of Central America are shaded in single colors but have Mexican states and Central American countries labeled. In the upper portion of North America, U.S. states (and territories) and Canadian provinces are shaded in various different colors and labeled. Major cities, bodies of water, and geographic features are marked (with relief shown by hachures and spot heights). On the reverse, two separate maps shows New Brunswick & Nova Scotia and the Dominion of Canada respectively. In each different provinces or regions are shaded in various colors. Cities, roads, bodies of water, and other features are marked and labeled on the maps. There are page numbers at the bottom of the sheet: 15 below the Dominion of Canada, 16 and 17 below North America, and 18 below New Brunswick & Nova Scotia. Prime meridians: Greenwich and Washington.